A co‐designed health information system implementation into residential aged care: A mixed‐method evaluation. Issue 2 (10th November 2022) - Bail, Kasia; Merrick, Eamon; Gibson, Diane; Hind, Alicia; Strickland, Karen; Redley, Bernice
Abstract: Introduction: Internationally, the adoption of technology into residential aged care settings has been slow and fraught with multiple challenges for residents, staff and service providers. The aim of this study was to evaluate the acceptability, efficiency, and quality of health information system implementation into aged care. Methods: Three‐stage, mixed‐methods participatory action research, concurrent with the natural experiment of a co‐designed health information system implementation into a 169‐bed aged care home in Australia. Data were collected pre‐, during, and post implementation between 2019 and 2021. Qualitative data included focus groups, interviews, and observations. Quantitative data included work observations, pedometers, record audits, incident reports and staff and resident surveys. There were 162 participants composed of 65 aged care residents, 90 staff, and 7 managers/consultants. Results: Improved work efficiency included reduced staff time searching for information (6%); reduced nurse time on documentation (20.4% to 6.4%), and 25% less steps. Documentation improvement included resident assessments (68% to 96%); resident‐focused goals (56% to 88%) and evaluations (31% to 88%). The staff reported being better equipped to manage the 'delicacies of dignity'. Conclusion: Implementation of a health information system into a residential aged care facility was associated with improved resident‐focused care and staff efficiency. Clinical relevance: Technology can support nurses and care staff to spend more time with residents in residential aged care homes, improve the quality of resident care, and assist meeting regulatory reporting requirements. Flexible and tailored co‐design strategies can enhance both effectiveness and success of technology implementation into residential aged care.